ململانێ سیاسى و سەربازییەکانى ئیمپراتۆرییەتى ئاشورى و دەوڵەتى ئیلام (١٣٦٥-٧٠٥پ.ز) و کاریگەرى لەسەر کوردستانى دێرین توێژینەوەیەکی مێژوویی-سیاسییە - عبدالصمد, د. ڕافدە عبداللە; عزیز, خوێندکاری ماستەر: زەردەشت عزت (Sulaimani Journal for Humanities, 2023)
The conflictions between the Assyrian and Elamite states were mainly sighted in those assaults which located on the strategic frontiers across their borderlands. These entrances were pathways for the trade routes and military assaults as well, such as: Dēr (Badrah), Tupliash (Mandali), Arabkha (Kirkuk), Ebekh (Hamrin) mountain, and Yalman (Hulwan) mountain. The Mesopotamian and Elaimte rulers had a long history of assaulting each other’s mainland. The conflictions were of two kinds: the direct ones which included military assaults to each other’s mainland, and the indirect assaults which consisted of their hegemony and rulership over the Babylon. The Elamites were supporting the Babylonians with financial aids and military empowerment in order to rebel against the Assyrian authority; their purpose was to disrupt the unity of Mesopotamia’s territories under the hegemony and authority of Assyria. This research applies the method of political history in presenting the events in a chronological order to illustrate the political and military conflictions between Assyria and Elam. It covers a long period of time from 1365 B.C through 911 B.C, by depending on authentic and reliable sources on this account. The research is consisted of three main sections: in the first section a brief discussion about Elam and its geographical place is presented; The second section focuses on the frontier struggles between Elam and Assyria from 1365 to 911 B.C; and the third. section discusses the conflictions of their interests from 911 to 705 B.C.